2014
DOI: 10.1155/2014/943786
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Dry Eye Disease and Physical Activity as well as Sedentary Behavior: Results from the Osaka Study

Abstract: Purpose. To assess the association of dry eye disease (DED) with physical activity and sedentary behavior. Methods. The cross-sectional survey conducted included Japanese office workers who use visual display terminals (n = 672). DED was assessed according to the Japanese Dry Eye Diagnostic Criteria, and participants were categorized into “definite DED,” “probable DED,” or “non-DED” groups based on the results of DED examinations. Physical activity and sedentary behavior of participants were assessed using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 30 publications
2
46
1
3
Order By: Relevance
“…13 Accordingly, not only systemic diseases (comorbidities) but also predisease conditions, including lifestyle factors, have been investigated in association with DED, and several pioneer works have been published. [14][15][16][17][18] First, several animal studies reported that excess oxidative stress is systemically associated with lacrimal dysfunction 19,20 and CR maintains tear secretion and reduces oxidative stress. 21 Next, the Osaka study, which conducted a cross-sectional study concerning dry eye among office workers, found several new systemic health factors associated with DED, such as metabolic syndrome, low exercise habit, sedentary lifestyle, poor sleep quality, and subjective happiness.…”
Section: Recent Progress In Japanmentioning
confidence: 99%
“…13 Accordingly, not only systemic diseases (comorbidities) but also predisease conditions, including lifestyle factors, have been investigated in association with DED, and several pioneer works have been published. [14][15][16][17][18] First, several animal studies reported that excess oxidative stress is systemically associated with lacrimal dysfunction 19,20 and CR maintains tear secretion and reduces oxidative stress. 21 Next, the Osaka study, which conducted a cross-sectional study concerning dry eye among office workers, found several new systemic health factors associated with DED, such as metabolic syndrome, low exercise habit, sedentary lifestyle, poor sleep quality, and subjective happiness.…”
Section: Recent Progress In Japanmentioning
confidence: 99%
“…These results are supported by a report from Kawashima et al that showed that DES are commonly reported by personal using video screens. [12] Similarly, Uchino et al reported an increased risk of DES when video screens are used for more than four hours. [8] Lee et al studied 6023 participants and showed that besides computer use, other environmental factors could influence the development of DES.…”
Section: Discussionmentioning
confidence: 96%
“…Environmental factors can include pollution, suspended particles, temperature, low humidity, exposure to video monitors. [8][9][10][11][12] In regard to the different occupations, an analysis of the Health and Nutrition Examination Survey in South Korea, found that professionals and technicians had increased risk of DES compared to farmworkers. [13] In India, Gupta et al reported a prevalence of DES of 33% among tannery workers.…”
Section: Introductionmentioning
confidence: 99%
“…Fortgeschrittene Gesichtsfelddefekte bei Glaukompatienten sind mit einem geringeren Maß an physischer Aktivität korreliert [25], wobei sich hierbei Ursache und Wirkung nicht sicher trennen lassen. Einen möglichen Einfluss könnte auch das trockene Auge haben, da bei sportlich aktiven Menschen seltener ein trockenes Auge vorliegt [26], das seinerseits eine diffuse Empfindlichkeitsminderung in der Perimetrie zur Folge haben kann. Der Effekt von sportlichen Ausdauerbelastungen lässt sich nicht nur auf den IOD reduzieren.…”
Section: Einflüsse Auf Ein Bestehendes Glaukomunclassified